A tool to measure the BIM Performance in Syrian higher education institutions - سعود لما (Latakia University Journal -Engineering Sciences Series, 2024)
The need to integrate BIM with education has increased recently to meet the labor market. Many international studies have provided tools to measure the performance of companies, organizations, and individuals wishing to adopt BIM, but there is a significant lack of tools to measure BIM performance for higher education institutions. The research is concerned with developing the BIM maturity matrix model as a tool for measuring and improving BIM performance in higher education institutions. The developed model is based on selecting the most appropriate criteria for evaluating BIM maturity and defining several levels of maturity, based on interviews with stakeholders in Syrian engineering companies and colleges. A tool is designed within Excel based on the developed model. The tool was applied to a case study of the Faculty of Civil Engineering at Tishreen University. Using the tool, the degree of maturity of the educational institution was measured, the strengths and weaknesses were explained, a plan was provided, and recommendations were made to improve the performance of BIM in the educational institution.